Dyslipidaemia, and mean blood cholesterol and triglycerides levels in the Portuguese population: a systematic review - Carreira,Helena (2012)
Introduction: Dyslipidaemia is a major risk factor for cardiovascular disease, the leading cause of death in Portugal. We aimed to critically summarize the evidence from studies that quantified the distribution of total cholesterol, cholesterol fractions and triglycerides, in order to estimate time trends in the Portuguese adult population. Methods: A systematic review was performed through Pubmed search up to January 2011. References and data extraction were performed independently by two researchers and 28 eligible studies identified. Ecologic estimates of mean total cholesterol, LDL, HDL, and triglycerides were computed by linear regression, adjusting for participants mean age, year of data collection and geographical coverage. Results: In 2005, the mean total cholesterol at 50 years of age was 215 mg/dL [95% confidence interval (95%CI): 210 to 219] among women and 219 mg/dL (95%CI: 206 to 232) among men. Between 1985 and 2005, the mean adjusted variation in total cholesterol per calendar year was 0.4 mg/dL (95%CI: -0.3 to 1.2) among women and -0.1 mg/dL (95%CI: -0.6 to 0.4) among men. Data on LDL, HDL and triglycerides covered a much narrower period, precluding analysis of time trends. In 2001 the adjusted mean levels of LDL, HDL and triglycerides were 132 mg/dL, 59 mg/dL and 111 mg/dL, respectively, among women, and 132 mg/dL, 49 mg/dL and 150 mg/dL, respectively, among men. Conclusions: Estimated mean cholesterol, respective fractions, and prevalence of dyslipidaemia suggest a high proportion of high-risk subjects in the Portuguese population. Between 1985 and 2005, mean total cholesterol did not vary significantly.